2005
DOI: 10.1002/jnr.20685
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone treatment, both as a single injection or repetitively, delays demyelination and enhances survival of Niemann‐Pick C mice

Abstract: Niemann-Pick C disease (NPC) is an irreversible neurodegenerative disorder without current treatment. It is thought to result from deficient intracellular cholesterol and/or ganglioside trafficking. We have investigated the effects of allopregnanolone treatments on survival, weight loss, motor function, magnetic resonance imaging (MRI), and neuropathology in the mouse model of NPC (Npc1(-/-) mice). We confirmed previous results showing that a single injection of 250 microg of allopregnanolone on postnatal day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 49 publications
7
44
0
Order By: Relevance
“…Our studies have now been repeated by other laboratories, which have demonstrated similar effects of allopregnanolone treatment on their colonies of NP-C mice (Ahmad, et al, 2005,Langmade, et al, 2006.…”
Section: Treatment Of Np-c Mice With Allopregnanolonesupporting
confidence: 58%
“…Our studies have now been repeated by other laboratories, which have demonstrated similar effects of allopregnanolone treatment on their colonies of NP-C mice (Ahmad, et al, 2005,Langmade, et al, 2006.…”
Section: Treatment Of Np-c Mice With Allopregnanolonesupporting
confidence: 58%
“…While administered in young mice (7 day-old Npc1 −/− mice), significant health improvements were observed including delayed degeneration and the life expectation of the animals was almost doubled [58][59][60]. Liu and colleagues (2009 [61]) reproduced equal observations when HPβCD alone was injected in 7-day-old Npc1 −/− mice.…”
Section: Niemann-pick Type C (Npc)mentioning
confidence: 99%
“…Ϫ / Ϫ mice ( 121,122 ). The ALLO was delivered via hydroxypropyl-␤ -cyclodextrin (HPBCD), but treatment with HPBCD alone had no effect in these studies.…”
Section: Mln64 and Menthomentioning
confidence: 99%